Inhibition of Notch signalling ameliorates experimental inflammatory arthritis. Issue 1 (19th November 2013) - Park, Jong-Sung; Kim, Seol-Hee; Kim, Kwangmeyung; Jin, Cheng-Hao; Choi, Ki Young; Jang, Jiyeon; Choi, Yuri; Gwon, A-Ryeong; Baik, Sang-Ha; Yun, Ui Jeong; Chae, Su Young; Lee, Seulki; et al.
Abstract : Objective: To test the hypothesis that Notch signalling plays a role in the pathogenesis of rheumatoid arthritis (RA) and to determine whether pharmacological inhibition of Notch signalling with γ-secretase inhibitors can ameliorate the RA disease process in an animal model. Methods: Collagen-induced arthritis was induced in C57BL/6 or Notch antisense transgenic mice by immunisation with chicken type II collagen (CII). C57BL/6 mice were administered with different doses of inhibitors of γ-secretase, an enzyme required for Notch activation, at disease onset or after onset of symptoms. Severity of arthritis was monitored by clinical and histological scores, and in vivo non-invasive near-infrared fluorescence (NIRF) images. Micro-CT was used to confirm joint destruction. The levels of CII antibodies and cytokines in serum were determined by ELISA and bead-based cytokine assay. The expression levels of cytokines were studied by quantitative PCR in rheumatoid synovial fibroblasts. Results: The data show that Notch signalling stimulates synoviocytes and accelerates their production of proinflammatory cytokines and immune responses involving the upregulation of IgG1 and IgG2a. Pharmacological inhibition of γ-secretase and antisense-mediated knockdown of Notch attenuates the severity of inflammatory arthritis, including arthritis indices, paw thickness, tissue damage and neutrophil infiltration, and reduces the levels of active NF-κB, ICAM-1, proinflammatory cytokines and matrix metalloproteinase-3 activity in the mouse model of RA. Conclusions: These results suggest that Notch is involved in the pathogenesis of RA and that inhibition of Notch signalling is a novel approach for treating RA.